Peningkatan Kesadaran Kekurangan Hemoglobin (Hb) pada Remaja di Sekolah Kalam Kudus II Jakarta - Alexander Halim Santoso; Giovanno Sebastian Yogie; Dean Ascha Wijaya; Fernando Nathaniel; Kasvana; Valentino Gilbert Lumintang (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Anemia is a blood disorder that often occurs in the productive age group, especially teenagers. The high prevalence of anemia is caused by several things, including a lack of awareness and knowledge about anemia and its prevention. The aim of this education is to increase awareness of hemoglobin deficiency in adolescents. This education provides basic information about anemia, including causes, symptoms and ways to prevent it, through counseling methods or seminars and leaflets which are attended by all class X students of SMA Kalam Kudus II Jakarta. Hope through this education, individual awareness about the importance of anemia and its prevention can be increased. Furthermore, the public understands anemia better and the efforts that can be made to prevent anemia, so it is hoped that this can be a beginning in reducing the incidence of anemia in society.